Adaptive Array Antenna with Modify Fruit Fly Optimization Algorithm for Finding Arrival Direction of Radio Signal - Lang, Alongkorn; Phongcharoenpanich, Chuwong; Kawdungta, Supakit (Engineering and Technology Horizons, 2022)
This paper presents an adaptive array antenna for radio signal direction finder application in the frequency of 2.4–2.5 GHz for troubleshooting co-channel interference issue in wireless local area network by using adaptive array antenna together with the modified fruit fly optimization algorithm (MFOA) to help finding Arrival Direction of Radio Signal. The proposed antenna consists of 4 elements of a microstrip patch planar array antenna, digital phase shifter, directional coupler and microcontroller. The simulation results show that the radiation pattern has main lobe of beamwidth 30 degrees and the main beam can be adjusted in both azimuth and elevation plane by controlling the phase of the signal on each element. The measurement results of the prototype antenna show that the radiation pattern can be adapted according to the simulation result by using the modified fruit fly optimization algorithm. The antenna should efficiently estimate the direction of arrival of the radio signal.